Investigating the feasibility of recovering urea from human urine - Marepula, Hlumelo (Department of Civil Engineering, 2022)
Background Urea is the most frequently used fertilizer by farmers globally and accounts for more than 50% of nitrogen-based fertilizer. It is produced indirectly through an energy intensive process known as the Haber-Bosch process. This process is often considered the most important invention in modern history because it contributed to the exponential growth in human population by providing food security. However, the process consumes 1 – 2% of the world's energy and contributes significantly to greenhouse emissions. The growth in human population has brought with it a multitude of challenges including waste management, resource depletion, greenhouse gas emissions and water scarcity. All these challenges are addressed in isolation and the synergistic benefits of integrating their solutions are not often realized. One way to integrate the solutions is to create a paradigm shift where ‘wastes', particularly human urine, are recognized as valuable resources, used to create value-added products. Human urine contains the key nutrients used in agriculture, nitrogen (N), phosphorous (P) and potassium, (K), of which N is the most dominant nutrient. Most of the N present in human urine is in the form of urea. Therefore, the aim of this work was to investigate the feasibility of recovering and purifying urea crystals from human urine using a novel ethanol evaporation and recrystallization process. This would be achieved by exploiting human urine for its N content to produce urea crystals in a sustainable way. In this investigation, it was hypothesized that urea can be recovered from urine by evaporating the water from it and dissolving the remaining solids in ethanol to purify the product. The impurities would then be isolated via filtration, resulting in a urea-ethanol solution that can be evaporated to isolate purer urea crystals. This is because most inorganic compounds found in urine are insoluble in ethanol while urea is highly soluble. The successful recovery of urea from human urine could potentially supplement the fertilizers produced from the Haber-Bosch process and address resource depletion. Challenges with waste management could also be addressed by introducing source separation of urine and faeces so that urine can be recycled for urea production. Because urine contains the highest nutrient load entering wastewater treatment plants (WWTPs), removing it from the wastewater flow could render the treatment process more energy efficient. Urea is a versatile product with uses spanning across different industries including agriculture, chemical, aviation, and automotive. Therefore, the success of this study has the potential to sustain urea production by manufacturing it in a responsible manner by utilizing a ‘waste' stream as a key input. Methodology Three objectives were investigated to recover urea from human urine using the solubility differences of urea and impurities in water and ethanol. The first objective involved conducting a series of thermodynamic simulations on five different urine compositions obtained fromliterature. The results of these simulations informed the conditions and parameters for the physical experiments that followed. Water removal from urine was simulated to determine at which point urea and other impurities would form. The simulation also predicted the potential yield and purity of the urea product. Thereafter, the addition of an intermediate filtration step at 99% and 95% water removal as a purification step was modelled to investigate whether the purity of urea improved. Following that, the solubility of pure urea in ethanol was simulated to determine the volume of ethanol required to dissolve and maximize the yield of urea. Physical experiments were then conducted to validate the results of the model. To improve the volume estimate of ethanol, the impact of the urine composition on the solubility of urea in ethanol was also investigated. From these results, the solubility of one of the compositions was chosen as a standard to conduct all physical experiments. The second objective involved recovering urea from different types of urine by operating within the parameters set by the thermodynamic model. Urea was recovered from a synthetic urine stream containing urea and inorganics (SI), a synthetic urine stream containing urea, organics, and inorganics (SO) and finally, a real urine stream (RU). The yields and purities of the three different experiments were compared and interrogated. In a final experiment, the solubility of urea in ethanol was investigated and compared to the thermodynamic model prediction. The model did not have the necessary database to model organics, other than urea. Therefore, another experiment was conducted to confirm the solubility of ethanol in urine containing organics. The final objective was the conceptual design of a small-scale urea recovery unit treating 1 m3 of urine per day. This was done to estimate the power requirements of such a system and the potential urea yield recovered per day. Finally, the profitability of the procedure was investigated by exploring different urea-based products. Key findings Thermodynamic modelling revealed that the point of crystallization of urea from urine was above approximately 99% water removal. Therefore, complete water removal was necessary to obtain the optimum amount of urea. An intermediate filtration step at 95% (58% purity) only improved the purity by 5% (from a purity of 53% at 100% water removed), while intermediate filtration at 99% (71% purity) improved the purity by 17%. An improvement of 5% was found to be insignificant relative to the final purity that could be achieved. In addition, intermediate filtration at 99% would not be practically feasible for the small volumes used in this study (1 L). Therefore, 100% water removal was used for these experiments. Based on this, a yield and purity of 100% and 53% was predicted by the model. The solubility of pure urea in ethanol was determined to be 40.98 g L-1 at 22°C, which was the average temperature in the laboratory. However, the impact of the urine composition on the solubility of urea in ethanol resulted in a higher solubility (50.05 g L-1 ). This value was therefore used for all physical experiments that followed and resulted in an ethanol volume requirement of ~232 mL. After complete water removal, yields of 91%, 84% and 93% and purities of 41%, 41%, and 43% were achieved for urea recovery from SO, SI and RU, respectively, which was lower that what the simulation predicted. After ethanol evaporation, yields decreased to 88%, 77% and 67% while the purities increased to 91%, 76% and 76% for SI, SO and RU, respectively. This demonstrated that the addition of ethanol improved the purity, but at a reduced yield. The loss in yield was likely due to a gradual decrease in pH during water removal, and prolonged evaporation times during ethanol evaporation, which could have resulted in enzymatic urea hydrolysis and loss of nitrogen as ammonia gas. To improve the solubility measurement, a physical experiment was conducted and revealed that the actual solubility of a typical urine stream containing organics is 56.7 g L-1 , demonstrating that the solubility increases with the presence of organics. Therefore, future work should use this higher solubility instead to further maximize the yield and purity. The conceptual design of a small-scale urea recovery system treating 1 m3 of urine per day had an estimated system power requirement of 8.4 kW m-3 . The potential recovery of urea per day was 15.61 kg (67% yield) at a purity of 76%. The system could be improved to recover 20.5 kg at 88% yield and 91% purity if the measures for improving the purity and yield are incorporated in the design. These measures include the selective removal of dissolved ions from the urea-ethanol solution via ion-exchange, increasing the temperature to speed up the evaporation process, and adding an intermediate filtration step at 99% water removal. Finally, through the analysis of different urea markets, the profitability of the procedure developed in this study was determined. It was concluded that a niche urea-rich liquid fertilizer would be the most valuable end-product to produce by redissolving the urea crystals in reclaimed water from the process. However, due to the small market of niche liquid fertilizers (~10% in the Cape Town region) it can only be produced in low volumes. Therefore, it was recommended that the remainder be used for diesel engine fluid production. The estimated profit per day (1 m3 of urine) from the production of 20 L of niche liquid urea fertilizer, 11.5 kg of solid calcium phosphate fertilizer and 44.6 L of diesel engine fluid was R3110. Conclusion and outlook This investigation demonstrated that the recovery of urea from human urine is achievable using the solubility differences in water and ethanol. All research objectives were fulfilled and the study described various opportunities for future work. This research developed an innovative method for recovering urea from human urine to potentially supplement the energy intensive Haber-Bosch process and discussed the possibility of producing alternative high-value products from human urine.